2009
DOI: 10.1097/pec.0b013e3181c07461
|View full text |Cite
|
Sign up to set email alerts
|

Additive Value of Nuclear Medicine Shuntograms to Computed Tomography for Suspected Cerebrospinal Fluid Shunt Obstruction in the Pediatric Emergency Department

Abstract: Over one third of pediatric ED patients evaluated with CT and CSF shuntograms required surgical management. Sensitivity was increased with CT and CSF shuntogram compared with CT alone. Prospective studies are required to assess the use of radiographic and nuclear medicine tests for the shunt evaluation in conjunction with the development of a clinical prediction rule for the pediatric emergency physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 22 publications
1
10
2
Order By: Relevance
“…In our study, negative predictive value of 50% was lower than that reported by Ouellette et al [8]. In their study, they found that CSF shuntograms showed abnormalities suggestive of CSF obstruction in 24 patients that required surgery (sensitivity 92%; negative predictive value 93%).…”
Section: Using Radionuclide Shuntogram Onlycontrasting
confidence: 55%
See 2 more Smart Citations
“…In our study, negative predictive value of 50% was lower than that reported by Ouellette et al [8]. In their study, they found that CSF shuntograms showed abnormalities suggestive of CSF obstruction in 24 patients that required surgery (sensitivity 92%; negative predictive value 93%).…”
Section: Using Radionuclide Shuntogram Onlycontrasting
confidence: 55%
“…The CT-Brain sensitivity in our study (100%) was higher than that reported by Ouellette et al [8] in their retrospective series of 69 patients, evaluated for suspected cerebrospinal shunt obstruction, as CT scans showed abnormalities suggestive of CSF shunt obstruction in only 20 patients from 26 true obstructive cases, with a sensitivity of 77%.…”
Section: Using Ct-brain Onlycontrasting
confidence: 53%
See 1 more Smart Citation
“…8 A less frequent emergency is a blocked cerebrospinal fluid shunt in a paediatric patient, for which nuclear medicine provides increased sensitivity. 9 If local reporting is impossible or impractical for emergency nuclear medicine, tele-nuclear medicine can usually provide an acceptable substitute.…”
Section: Clinical Tele-nuclear Medicinementioning
confidence: 99%
“…The sensitivity, specificity, and accuracy of the radionuclide shuntogram have been described to be as high as 97, 90, and 93%, respectively, in a study by Graham et al [22] that included the analysis of 192 radionuclide CSF shunt studies. In the modern age, the radionuclide CSF shunt study remains a clinically useful and important adjunct diagnostic study to CT and/or MRI for the diagnosis of shunt obstruction or malfunction [21,[23][24][25] .…”
Section: Ultrasoundmentioning
confidence: 99%